Etika Komunikasi dalam Media Sosial Sesuai Tuntutan Al-Qur an - Rinwanto Rinwanto; Hidayatus Sholihah; Nurul Hakim; Mufid Syakhlani (Journal of Communication Studies, 2021)
Abstract This paper discusses the phenomenon of the development of communication tools in the ancient era until it has grown rapidly until now. Many uncovered stories that are not true from people who are not responsible, either from certain groups or from personal interests. Communication from social media is very dangerous if it is not accompanied by proper ethics in communicating, especially in social media. AS-Syaukani, for example, defines the keyword al-bayan as the ability to communicate. Besides that, in the al-quran there is another keyword, namely qoul. The commands to say in the al-quran and hadith are an indication of the obligation for Muslims to apply the nature of honesty and correct speech which in the concept of al-quran is known as qaulan sadidan.